A Post-Pandemic Needs Assessment Survey of Three Adopted Barangays of AIMS: Basis in the Development of Institutional Outreach Plans and Programs - Brosas , Jeffrey F.; Almazan, Precious Ann G.; Pardo, Rossielyn R. (Future Science / FSH-PH Publications, 2023)
The community needs assessment of three adopted barangays of the Asian Institute of Maritime Studies served as a guide for the Center for Outreach Extension Development in enhancing strategic plans and programs, and in preparing necessary resources and funds. In assessing the needs of residents of the three adopted barangays, a descriptive-survey method was applied since it aims to gather the present conditions and situations of the barangays’ residents. The Community Needs Assessment survey instrument involves questions relevant to the subjects of the research and distributed to the respondents. Respondents are representative of each family in the three adopted community beneficiaries. In Barangay 13, there were 21 families; in Barangay Julugan IV, there were 24 families and in Barangay La Isla Bonita, there were 14 families. Convenience sampling was used and families living in the nearby vicinity of the Barangay Hall were the participants. From the result of the survey, most of them were high school graduates and unemployed. Likewise, participants cannot identify their own skills so the majority of the families lack a source of income, and this is a common problem within the three barangays. The suggested trainings that the respondents were willing to attend are training for electronic/ computer/cellphone repair, cooking, dressmaking, and practical electricity. The additional training to the existing program could help families to have a source of income or to be employed. Thus, the members of the adopted community could have a better standard of living through skills trainings.